Technology to enhance learning: The Jordanian experience - Khasawneh, Mohammad M.F.; Ibrahim, Huda (2012)
The rapidly growth of Information and Communication Technologies (ICTs) has changed the routine life in the world. Developing nations see the economic prosperity in developed nations by development of associated information technology and development of a knowledge society.Jordan, as one of the developing countries, highly values the importance of Higher Education Institutions (HEIs) and their role in achieving an economic prosperity through the development of human resources.Unfortunately, the adoption and usage of ICT in teaching and learning process is quite low among the academic staff in the public HEIs in Jordan.The main purpose of this study is to present the differences between academic staffs’ demographic characteristics and the usage of common technologies such as computers, Internet, mobile phone, and personal digital assistant (PDA) that affects their adoption and usage of ICT in the teaching and learning process. The results show there are some significant differences between demographic factors and such common technologies.Besides, the study presents the current status of ICT usage in public HEIs in Jordan among academicians.